Electric Power Supply Quality in ship systems: an overview. (15th April 2008) - Prousalidis, J.; Styvaktakis, E.; Kanellos, F.; Perros, S., E. Sofras
Power Supply Quality (PSQ) has become an important concern for ship electric systems. Thus, deviations of voltage from nominal values and wave-shapes could cause several problems onboard. Considering that ship system electrification eventually dominates according to the All Electric Ship concept, PSQ will be a key-factor of the normal operation, survivability and safety aboard. The paper provides a coherent description and categorisation of the PSQ phenomena (causes, consequences, characteristic parameters etc.) highlighting similarities and differences between terrestrial systems and ship systems in terms of these phenomena. This overview is enriched by cross-references to relevant standards applied in shipboard applications.